2010
DOI: 10.1093/cvr/cvq249
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled receptor kinase 2 and arrestin2 regulate arterial smooth muscle P2Y-purinoceptor signalling

Abstract: AimsProlonged P2Y-receptor signalling can cause vasoconstriction leading to hypertension, vascular smooth muscle hypertrophy, and hyperplasia. G protein-coupled receptor signalling is negatively regulated by G protein-coupled receptor kinases (GRKs) and arrestin proteins, preventing prolonged or inappropriate signalling. This study investigates whether GRKs and arrestins regulate uridine 5′-triphosphate (UTP)-stimulated contractile signalling in adult Wistar rat mesenteric arterial smooth muscle cells (MSMCs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 28 publications
8
63
1
Order By: Relevance
“…Our finding supports this possibility that both small-molecule inhibition and knockdown of GRK2 enhance photorelaxation. Consistent with our results, GRK2 seems to be the principal GRK in regulating vascular smooth muscle-associated GPCRs (28), including α 1 -adrenergic (29), endothelin (30), purinergic (31), and β-adrenergic receptors (32).…”
Section: Discussionsupporting
confidence: 85%
“…Our finding supports this possibility that both small-molecule inhibition and knockdown of GRK2 enhance photorelaxation. Consistent with our results, GRK2 seems to be the principal GRK in regulating vascular smooth muscle-associated GPCRs (28), including α 1 -adrenergic (29), endothelin (30), purinergic (31), and β-adrenergic receptors (32).…”
Section: Discussionsupporting
confidence: 85%
“…The expression plasmid encoding FLAGtagged b-arrestin1 was a generous gift from Robert Lefkowitz (Luttrell and Lefkowitz, 2002). The expression plasmid encoding bovine GRK2 was a generous gift from Jon Willets (Morris et al, 2011), and the expression plasmid encoding bovine GRK2-K220R was from Addgene (plasmid number 14691; Cambridge, MA). Either 10 27 M SDF-1a (R&D Systems, Minneapolis, MN) or 10 ng/ml PMA (EMD Millipore, Billerica, MA) was used for cell stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…Since several reports suggest that b-arrestins associate with GRKs, and that these proteins function together to regulate GPCRs (Willets et al, 2001;Busillo et al, 2010;Morris et al, 2011), we asked if GRK2 also participates in regulating b-arrestin1-dependent CXCR4 internalization in neuroblastoma cells. GRK2 was endogenously expressed in both SH-SY5Y and SK-N-SH cells (Fig.…”
Section: Sdf-1 Uses B-arrestin1 and Cxcr4 Structures In Neuroblastomamentioning
confidence: 99%
“…Similarly, in mouse mesenteric arteries, there was evidence for contractile responses mediated by both P2Y 6 and P2X 1 receptors, because responses to UTP and UDP were reduced by a selective P2Y 6 antagonist, and a contractile response to a,b-meATP was blocked by the P2X 1 receptor antagonist NF023 (Koltsova et al, 2009). G proteincoupled receptor kinase 2 and arrestin-2 regulate UTPstimulated P2Y 2 receptors mediating constriction of rat mesenteric artery smooth muscle (Morris et al, 2011). Whole-cell voltage clamp studies of guinea pig mesenteric terminal arterioles have suggested that ATP activation of Ca 2+ currents was mediated by P2Y 1 -and P2Y 11 -like receptors (Morita et al, 2002).…”
Section: Mesenteric Vesselsmentioning
confidence: 99%
“…Similarly, the use of knockouts and antisense oligonucleotides showed the functional expression of vasocontractile P2Y 4 and P2Y 6 but not P2Y 2 receptors in mouse mesenteric arteries and cerebral arterioles (Vial and Evans, 2002;Bar et al, 2008;Kauffenstein et al, 2010a;Brayden et al, 2013). In contrast, in rat mesenteric arteries, small interfering RNA (siRNA) knockdown of P2Y 2 mRNA demonstrated the almost exclusive involvement of P2Y 2 receptors in contraction to UTP (Morris et al, 2011). This demonstrates pronounced species differences in the expression of vasocontractile P2Y receptors, which were not detected through the use of pharmacology alone.…”
Section: Introductionmentioning
confidence: 99%